2002
DOI: 10.1074/jbc.m108008200
|View full text |Cite
|
Sign up to set email alerts
|

The Nedd8-conjugated ROC1-CUL1 Core Ubiquitin Ligase Utilizes Nedd8 Charged Surface Residues for Efficient Polyubiquitin Chain Assembly Catalyzed by Cdc34

Abstract: Lysine 48-linked polyubiquitin chains are the principle signal for targeting proteins for degradation by the 26 S proteasome. Here we report that the conjugation of Nedd8 to ROC1-CUL1, a subcomplex of the SCF-ROC1 E3 ubiquitin ligase, selectively stimulates Cdc34-catalyzed lysine 48-linked multiubiquitin chain assembly. We have further demonstrated that separate regions within the human Cdc34 C-terminal tail are responsible for multiubiquitin chain assembly and for physical interactions with the Nedd8-conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
89
2

Year Published

2005
2005
2009
2009

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 38 publications
4
89
2
Order By: Relevance
“…This is contrary to published studies of Cdc34 binding to Cul1 and Roc1. 15 Paradoxically, the binding of the Cdc34 5 PT MUT A to Cul1 and Roc1 was reduced compared to WT Cdc34 and the Cdc34 1-200 mutant, while the binding of the Cdc34 5 PT MUT E to Cul1 and Roc1 was similar to WT Cdc34 (Fig. 3A, B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is contrary to published studies of Cdc34 binding to Cul1 and Roc1. 15 Paradoxically, the binding of the Cdc34 5 PT MUT A to Cul1 and Roc1 was reduced compared to WT Cdc34 and the Cdc34 1-200 mutant, while the binding of the Cdc34 5 PT MUT E to Cul1 and Roc1 was similar to WT Cdc34 (Fig. 3A, B).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro binding studies of Cdc34 with Cul1 and Roc1 and Cdc34 auto-ubiquitination assays suggest that Cdc34 is recruited to the SCF through an interaction with a Cul1-Roc1 heterodimer. 15,36 More specifically, in vitro binding studies indicate that residues 195-236 of Cdc34 are required for maximal binding to GST-Roc1-Cul1 . 15 This suggested to us that the Cdc34 1-200 defect in complementation and p27 Kip1 ubiquitination might be attributable to an inability of the truncated Cdc34 to bind efficiently to the SCF through its association with Cul1-Roc1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that NEDD8 modification facilitates the recruitment of the E2 ubiquitinconjugating enzyme to the SCF complex and mediates the dissociation of p120 CAND1 an inhibitor of SCF ligase activity. 11,12 In Drosophila NEDD8 mutants, there is an accumulation of protein levels for the cell cycle regulator, Cyclin E (CycE), and for the signal transduction effectors, Cubitus interruptus (Ci), and Armadillo (Arm). 13 Recently, NEDD8 has been shown to be incorporated into a variety of ubiquitinated inclusions, including the neurofibrillary tangles present in AD.…”
mentioning
confidence: 99%